2020
DOI: 10.1016/j.ijcha.2020.100608
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrhythmias and In-hospital mortality amongst patients with takotsubo cardiomyopathy: A retrospective study in an Italian population

Abstract: Highlights: Takotsubo cardiomyopathy was more common in women and the mortality rate was 2.2%. Ventricular arrhythmias were the strongest predictor of mortality. Age was associated with increased mortality in women with takotsubo cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In a subanalysis of sex in the same study, age predicted in-hospital mortality in female patients (OR 1.06, 95% CI 1.04-1.08) but did not have the same predictive value among male patients (P = 0.08). 28 Other studies suggest that age is not associated with shortterm mortality in TCM patients (Table 2). 18,19,23,27,38,63,69,70 After a multivariable logistic regression analysis, Cammann et al found no significant difference among different age groups in in-hospital mortality (age 51-74 years old as reference, ≤50 years old, P = 0.14; ≥75 years old, P = 0.75) or 60 day mortality (P = 0.16).…”
Section: Agementioning
confidence: 95%
See 2 more Smart Citations
“…In a subanalysis of sex in the same study, age predicted in-hospital mortality in female patients (OR 1.06, 95% CI 1.04-1.08) but did not have the same predictive value among male patients (P = 0.08). 28 Other studies suggest that age is not associated with shortterm mortality in TCM patients (Table 2). 18,19,23,27,38,63,69,70 After a multivariable logistic regression analysis, Cammann et al found no significant difference among different age groups in in-hospital mortality (age 51-74 years old as reference, ≤50 years old, P = 0.14; ≥75 years old, P = 0.75) or 60 day mortality (P = 0.16).…”
Section: Agementioning
confidence: 95%
“…16 Despite female sex being a strong risk factor for TCM, most of the studies we identified suggest that it is associated with favourable short-term outcomes in TCM (Table 1). Some studies have found that male patients have poorer short-term outcomes, such as higher rates of in-hospital mortality 19,[23][24][25][26][27][28][29][30][31] and complications. 18,20,32 One retrospective study of 14 639 patients found that female patients had a lower rate of in-hospital mortality [odds ratio (OR) 0.521, 95% confidence interval (CI) 0.389-0.699].…”
Section: Factors Affecting Prognosis Of Takotsubo Cardiomyopathy Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few cases describe the normalization of AV conduction related to TCM [7][8][9], and this is the first case that reports it just a few hours after admission. Recent data suggest that advanced atrioventricular block is not associated with worse in hospital outcomes unlike what occurs with ventricular arrhythmias [10]. Two years after the admission, the patient remains asymptomatic with a first-degree AV block on the electrocardiogram.…”
Section: Discussionmentioning
confidence: 87%
“…The Italian group recently demonstrated that male sex and ventricular arrhythmias were associated with in-hospital mortality in patients hospitalized for Takotsubo syndrome [3] . Data of arrhythmias would further strengthen the implication of their study.…”
mentioning
confidence: 99%